Unblurring the Market for Vision Correction: A Willingness to Pay Experiment in Rural Burkina Faso - Michael Grimm; Renate Hartwig (Institute of Labor Economics (IZA), 2018)
We assess the willingness to pay (WTP) for eyeglasses in an adult population in rural Burkina Faso using a variant of the Becker-DeGroot-Marschak (BDM) method. We combine the BDM approach with video and deferred payment options to analyze the role of information and liquidity constraints. Furthermore, we exploit variation in reservation and transaction prices to study potential screening and sunk cost effects. Our main results show that, consistent with the over-exclusion perspective documented for essential health products, the willingness to pay for glasses is low, amounting to 20% of the current market price. Information provided through a video raises the willingness to pay for corrective glasses by 16%. In contrast, deferred payment does not affect the willingness to pay. Finally, we find no evidence of screening or sunk cost effects. Overall our results lend support to subsidization of eyeglasses in a resource poor setting.
Keywords: D11; D12; D83; I15; 330; eyeglasses; information constraint; liquidity constraint; willingness to pay; Burkina Faso